Design and synthesis of a novel coumarin-based framework as a potential chemomarker of a neurotoxic insecticide, azamethiphos. (10th February 2020) - Bhasin, Aman K. K.; Raj, Pushap; Chauhan, Pooja; Mandal, Sanjay K.; Chaudhary, Savita; Singh, Narinder; Kaur, Navneet
Abstract : A coumarin based receptor has been synthesised and its organic nanoparticles were prepared. Further, these nanoparticles were explored as a chemosensor for copper(ii ) ions and azamethiphos. Abstract : Selective affinity of a novel coumarin-functionalized fluorescent sensor, 8-(( E )-((thiophen-2-yl)methylimino)methyl)-7-hydroxy-4-methyl-2 H -chromen-2-one (L ), to copper(ii ) ions via fluorescence quenching in HEPES buffer at pH 7.4 has been demonstrated. This coordination chemistry between the coumarin-based ligand L and copper(ii ) ions has been subsequently exploited for the generation of a unique chemical ensemble, L ·Cu 2+, which qualifies the former as a sensitive and selective fluorogenic sensor for the toxic organophosphate pesticide azamethiphos in aqueous medium. The sequestering of the native fluorescence of receptor probe L upon entrapment of copper(ii ) within the former was altered upon sequential administration of azamethiphos into the environment of the host complex, L ·Cu 2+ . The physico-chemical interactions between the sensor complex L ·Cu 2+ and azamethiphos, as corroborated by 31 P NMR studies and fluorescence spectroscopy, serve as the basis for ideal chemical discrimination of azamethiphos, amongst a pool of several ecotoxic organophosphate pesticides.